Recurrent Cardiac Arrest With Negative Stress Test: An Unusual Presentation of Catecholaminergic Polymorphic Ventricular Tachycardia - Annor, Ama K. (JACC Case Rep, 2020)
Catecholaminergic polymorphic ventricular tachycardia is a genetic disorder that causes ventricular tachyarrhythmias via increased release of intracellular calcium. The standard diagnostic measure is an exercise stress test that reveals ventricular ectopy. We present an extraordinary case marked by a normal stress test and no relation to exertion. (Level of Difficulty: Intermediate.)